Repair of Tea Polysaccharide Promotes the Endocytosis of Nanocalcium Oxalate Monohydrate by Damaged HK-2 Cells - Li, Chuang-Ye (Oxid Med Cell Longev, 2020)
Endocytosis is a protective mechanism of renal epithelial cells to eliminate retained crystals. This research investigated the endocytosis of 100 nm calcium oxalate monohydrate crystals in human kidney proximal tubular epithelial (HK-2) cells before and after repair by four kinds of tea polysaccharides with molecular weights (MWs) of 10.88 (TPS0), 8.16 (TPS1), 4.82 (TPS2), and 2.31 kDa (TPS3), respectively. When HK-2 cells were repaired by TPSs after oxalic acid injury, the cell viability, wound healing ability, mitochondrial membrane potential, percentage of cells with endocytosed crystals, and dissolution rate of the endocytosed crystals increased; the cell morphology recovered; and the reactive oxygen level and lactate dehydrogenase release decreased. Most of the endocytosed crystals were found in the lysosomes. The repair effects of the four TPSs were ranked in the following order: TPS2>TPS1>TPS3>TPS0. TPS2 with moderate MW presented the optimal repair ability and strongest ability to promote endocytosis.